Semirigid Cantilever Extension System for Splinting Implants: A Clinical Report - Raissa Micaella Marcello Machado; Luciana de Rezende Pinto; Otacílio Luiz Chagas Júnior; Fernanda Faot (Hindawi Limited, 2014)
In mandibular edentulous patients, treatment based on immediate loading with rigid splinting in the mandible is well accepted; however, it is cost and time dependent, which sometimes limits this type of rehabilitation. To overcome these problems, the technique of immediate loading using a semirigid splinting extension system has been developed. Its advantages include low cost, technical feasibility, and reduced clinic time. This clinical report presents the applicability and the predictability of semirigid splinting of implants in the mandibular arch of an edentulous patient using a distal extension bar prosthesis system.